THE EFFECTS OF SPEED AND PATTERNS OF WALKING ON AEROBIC CAPACITY AND CORONARY HEART DISEASE RISK PROFILES IN MIDDLE-AGED OVERWEIGHT AND OBESE INDIVIDUALS - Sitha Phongphibool (Chulalongkorn University, 2016)
177 pages